2011
DOI: 10.1177/0042098011405694
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Housing Assistance on the Employment Outcomes of Labour Market Programme Participants in Australia

Abstract: This paper examines whether the employment outcomes of Australian labour market programme participants vary according to whether they receive housing assistance. This issue attracted attention when a series of US studies showed that clients of welfare-to-work programmes are more likely to achieve positive employment outcomes if housing assistance is also received. This paper tracks the employment outcomes of labour market programme participants utilising six waves of data from the Household Income and Labour D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A recent Productivity Commission report (2019) also considers CRA to be well targeted to those who need the most assistance. Feeny, Ong et al (2012) find that housing assistance status has little impact on employment outcomes. These studies have focused on the effects of the design of housing assistance on employment participation and on wellbeing outcomes (Parkinson, Cigdem et al 2013).…”
Section: Commonwealth Rent Assistance and Housing Instability/affordamentioning
confidence: 86%
“…A recent Productivity Commission report (2019) also considers CRA to be well targeted to those who need the most assistance. Feeny, Ong et al (2012) find that housing assistance status has little impact on employment outcomes. These studies have focused on the effects of the design of housing assistance on employment participation and on wellbeing outcomes (Parkinson, Cigdem et al 2013).…”
Section: Commonwealth Rent Assistance and Housing Instability/affordamentioning
confidence: 86%
“…As part of a wider evaluation of the effects of housing status on transitions to employment, the study compared the effects of participation in three categories of Mutual Obligation activity in any year prior to 2004 on the probability of employment in 2004: 'employment assistance' (comprising mainly Job Network Intensive Assistance or Job Search Training -note that at that time Intensive Assistance was an alternative option to Mutual Obligation for those unemployed for six months), 'training' (comprising mainly part time study or literacy training) and 'employment and community participation' (comprising mainly Work for the Dole, part time paid work, or voluntary work). The study found that compared with 'employment assistance', the average employment outcome of 'training' programs (measured in 2004) was 10.6 percentage points lower and that of 'employment and community participation' was 12.7 percentage points lower (Feeny et al 2008). A potential limitation of this study is that the HILDA survey relied on respondent's recall of participation in programs (including participation prior to the first year of the survey).…”
mentioning
confidence: 87%
“…Using the HILDA dataset, the Australian research community has advanced knowledge of housing affordability considerably in recent years. Insights from recent HILDAcentred studies include Buddelmeyer, Lee et al (2010), who found that workers in low-paid employment are not at higher risk of unemployment than higher paid workers, and Feeny, Ong et al (2012) who reported that housing assistance payments had little or no impact on individuals' employment outcomes. Lodewijks (2011) found that financial constraints and low levels of wealth boosted the incidence of job moves for men under the age of 40 and argued that this was a wage growth strategy.…”
Section: Existing Researchmentioning
confidence: 99%